Pemilihan Umum Lebanon 2022: Akhir Taif Accord dan Selebrasi Demokrasi? - Gadubun, Cahyani; Basyar, Muhammad Hamdan (UI Scholars Hub, 2022)
Lebanon has experienced a long political stalemate due to sectarian tensions. The negative effect of confessionalism theory makes sectarian identity stronger and ultimately results in instability and fragility of the Lebanese political system. The opposition demands political and economic reforms. The Lebanese general election, 15 May 2022, is expected to bring goodness to the Lebanese people. This paper wants to analyze the possibility of these changes. The results of the research show that the transformation of Lebanon towards a democratic government is always hindered by sectarian conflicts within the government. But through the results of the 2022 elections, there is hope for political reform in Lebanon. The election of 13 independent MPs is a celebration of democracy in the Middle East. This is a very important small step towards more peaceful and democratic political reforms in Lebanon.